Physical activity levels of Malaysian vegetarians and its associated factors: a cross-sectional study - Ching, Yuan Kei; Appukutty, Mahenderan; Gan, Wan Ying; Chan, Yoke Mun; Chin, Yit Siew (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Literatures suggest that insufficient physical activity as one of the contributors to non-communicable chronic diseases; nevertheless, data on the physical activity level is sparsely reported among individuals practising a vegetarian diet in Malaysia. The current study aims to determine the prevalence of insufficient physical activity and its association with socio-demographic factors, lifestyle factors and body weight status among 273 individuals practising a vegetarian diet in Klang Valley, Malaysia. Methods: A set of self-administered questionnaire was distributed to all vegetarians and their data on physical activity was determined using the Global Physical Activity Questionnaire (GPAQ). Results: The average years of practising vegetarianism was 14.2±9.6 years, and most of the vegetarians were practised ovo-vegetarian diet (44.0%). A majority of them were Chinese (54.9%) and female (64.8%), with an average age of 47.5 ± 13.1 years. The prevalence of overweight and obesity were 27.5% and 8.1%, respectively. According to GPAQ, about two in five vegetarians (46.2%) were having insufficient physical activity. Being females, older age, Chinese, married individuals, and those with high total household income level were found to be significantly associated with low physical activity level among Malaysian vegetarians (p <0.05). Conclusion: Since insufficient physical activity is one of the factors contributing to non-communicable chronic diseases, it is crucial to educate the importance of physical activity on overall health status, specifically for those who at risk of physically inactive. In addition, future studies can focus the causal associations based on the currently identified factors and physical activity levels, which can help to develop an effective intervention program among Malaysia vegetarians.